2015
DOI: 10.1111/jnc.13025
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter oligomerization: impact of combining protomers with differential cocaine analog binding affinities

Abstract: Previous studies point to quaternary assembly of dopamine transporters (DATs) in oligomers. However, it is not clear whether the protomers function independently in the oligomer. Is each protomer an entirely separate unit that takes up dopamine and is inhibited by drugs known to block DAT function? In this work, human embryonic kidney 293 cells were co-transfected with DAT constructs possessing differential binding affinities for the phenyltropane cocaine analog, [3H]WIN35,428. It was assessed whether the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Dominant negative mutants of the human dopamine transporter (DAT) have been shown to reduce the function of co-expressed WT transporters, without any effect on trafficking to the plasma membrane [22]. Further functional studies have supported co-operativity, or cross-talk, between individual protomers in DAT oligomers [23]. Additional supportive evidence for this cross-talk has come from studies on fusion proteins of the serotonin transporter (SERT) with GAT-1 [24].…”
Section: The Leut Superfamilymentioning
confidence: 99%
“…Dominant negative mutants of the human dopamine transporter (DAT) have been shown to reduce the function of co-expressed WT transporters, without any effect on trafficking to the plasma membrane [22]. Further functional studies have supported co-operativity, or cross-talk, between individual protomers in DAT oligomers [23]. Additional supportive evidence for this cross-talk has come from studies on fusion proteins of the serotonin transporter (SERT) with GAT-1 [24].…”
Section: The Leut Superfamilymentioning
confidence: 99%
“…Our previous study demonstrated an influence of DAT protomer composition on the properties of a DAT inhibitor (Zhen et al . ). When DAT oligomers contained combinations of certain protomers with differential affinity for the cocaine phenyltropane analog CFT ((‐)‐2‐β‐carbomethoxy‐3‐β‐(4‐fluorophenyl) tropane = WIN 35 428), the resulting binding affinity differed from that found under conditions where heterooligomers were not present.…”
mentioning
confidence: 97%
“…Whether oligomeric complexes are the predominant state of DAT orientation in vivo is unknown, but some evidence supports the existence of DAT tetramers within striatal membranes (Milner et al, 1994). However, the potential significance of oligomers has been demonstrated by recent work showing that, under certain conditions, DAT protomers within an oligomeric complex affect the conformational state of one another, altering DA transport activity and sensitivity to stimulants historically classified as DAT reuptake inhibitors such as cocaine (Zhen et al, 2015). The size, composition, and distribution of DAT oligomeric complexes may therefore influence the sensitivity of particular dopaminergic neurons to stimulants and any subsequent toxicity.…”
mentioning
confidence: 99%